2003
DOI: 10.3171/jns.2003.99.6.0960
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment of ruptured dissecting aneurysms of the vertebral artery during the acute stage

Abstract: The factors that determine the appropriate treatment for ruptured dissecting aneurysms of the VA are tolerance of a test occlusion and the site of dissection. Favorable patient outcomes can be achieved when this algorithm is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
103
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 19 publications
0
103
0
Order By: Relevance
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical treatment includes trapping the aneurysm, proximal ligation of the vertebral artery (VA ), or wrapping the aneurysm. Previous reports have suggested that endovascular parent artery occlusion is a safe and effective treatment for VAD [1][2][3][4][5][6][7][8][9][10]. Although some case series have reported on the feasibility of stent replacement, endovascular internal trapping has been performed in most of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Kitanaka et all reported that a very high rate of postoperative complication with major causes of disability were attributable to lower cranial nerve palsy and associated condition as prolonged intubation and tube feeding [2,5,6]. Vertebral artery recanalization by antegrade flow, coil compactation, coil loop migration, intra-stent thrombosis and distal thrombembolism have been also reported as complications of endovascular treatments.…”
Section: Discussionmentioning
confidence: 99%
“…4,12) Therefore, surgical repair of the lesion is best performed in the acute stage. 4,5) However, several treatment strategies have been proposed for ruptured VA dissecting aneurysm associated with occlusion of the parent artery. Medical treatment of a patient with occlusion of the affected artery 4 months after the onset resulted in no rebleeding for 16 months after the first ictus.…”
Section: Discussionmentioning
confidence: 99%